Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.semcdb.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles in cancer: A review of recent developments and the potential for clinical application

Abstract: Once thought of as inert remnants of cellular processes, the significance of membrane vesicles is now expanding as their capacity to package and transfer bioactive molecules during intercellular communication is established. This ability to serve as vectors in the trafficking of cellular cargo is of mounting interest in the context of cancer, particularly in the dissemination of deleterious cancer traits from parent cells to recipient cells. Although microparticles (MPs) contribute to the pathogenesis of cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 69 publications
1
54
0
Order By: Relevance
“…MPs as derivate of cellular membrane are discussed powerful paracrine regulators of target cell functions [30][31][32]. Indeed, MPs possess a wide spectrum of biological effects on intercellular communication by transferring different molecules (autoantigens, cytokines, mRNA, iRNA, hormones, tissue coagulation factors, and surface receptors) able to modulate other cells affected growth of tissue, reparation, vasculogenesis, inflammation, apoptosis, infection, The number of red blood cell-derived microparticles in predicting periprocedural adverse effects in acute ST-segment elevation myocardial infarction patients Copyright: © 2017 Berezin and malignancy [33][34][35][36][37][38][39].…”
Section: Biological Role and Function Of Mpsmentioning
confidence: 99%
“…MPs as derivate of cellular membrane are discussed powerful paracrine regulators of target cell functions [30][31][32]. Indeed, MPs possess a wide spectrum of biological effects on intercellular communication by transferring different molecules (autoantigens, cytokines, mRNA, iRNA, hormones, tissue coagulation factors, and surface receptors) able to modulate other cells affected growth of tissue, reparation, vasculogenesis, inflammation, apoptosis, infection, The number of red blood cell-derived microparticles in predicting periprocedural adverse effects in acute ST-segment elevation myocardial infarction patients Copyright: © 2017 Berezin and malignancy [33][34][35][36][37][38][39].…”
Section: Biological Role and Function Of Mpsmentioning
confidence: 99%
“…Recent investigations have been shown that MPs as derivate of cellular membrane are discussed powerful paracrine regulators of target cell functions [27][28][29]. Indeed, MPs possess a wide spectrum of biological effects on intercellular communication by transferring different molecules (autoantigens, cytokines, mRNA, iRNA, hormones, tissue coagulation factors, and surface receptors) able to modulate other cells affected growth of tissue, reparation, vasculogenesis, inflammation, apoptosis, infection, and malignancy.…”
Section: Biological Role and Function Of Mpsmentioning
confidence: 99%
“…Gong and co-workers (2015) emphasized the clinical importance of MPs on regarding drug resistance and metastasis. On their review, the MPs potential on cancer diagnosis and prognosis was also discussed (Gong et al 2015). In addition, El Andaloussi and co-workers (2013) largely reviewed the role of MPs in tumor biology.…”
Section: Microparticles and Cancer Resistancementioning
confidence: 99%